1986
DOI: 10.1002/eji.1830160720
|View full text |Cite
|
Sign up to set email alerts
|

B cell activation by the nontransforming P3HR‐1 substrain of the Epstein‐Barr virus (EBV)

Abstract: The P3HR-1 substrain of Epstein-Barr virus does not transform B cells. This defect is known to be determined by the loss of the coding sequence for the nuclear antigen EBNA-2. The virus can attach to and enter resting B cells. The initial events after EBV infection are reminiscent of those induced by polyclonal B cell activators. Similar to the effect of these, P3HR-1 virus lowers membrane IgD expression on B cells and abrogates the transient elevation of activation markers BB-1 and LB-1 induced by the culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1987
1987
2006
2006

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Triggering of BCGF responsiveness was observed over a wide range of virus dilutions. The effect was smaller compared to that induced by anti-IgM antibodies (not shown), but comparable to that induced by P3HR1 virus [9] and F(ab')* anti-gpl40 antibodies ~7 1 . that this interaction can provide an inhibitory signal for cell proliferation [33].…”
Section: Bcgf Responsiveness Induced By Uv-inactivated Ebvsupporting
confidence: 43%
See 1 more Smart Citation
“…Triggering of BCGF responsiveness was observed over a wide range of virus dilutions. The effect was smaller compared to that induced by anti-IgM antibodies (not shown), but comparable to that induced by P3HR1 virus [9] and F(ab')* anti-gpl40 antibodies ~7 1 . that this interaction can provide an inhibitory signal for cell proliferation [33].…”
Section: Bcgf Responsiveness Induced By Uv-inactivated Ebvsupporting
confidence: 43%
“…Our results demonstrate that B lymphocyte infected with nontransforrning UV-inactivated B95-8 virus and P3HR1 virus [9] became responsive to T cell-derived growth factors. Mouse B cells, operationally defined as resting on the basis of their small size and low RNA content, were shown to respond to BCGF [41,421.…”
Section: Discussionmentioning
confidence: 90%
“…Indeed, we have shown previously that simple virus binding to the B cell is sufficient to induce a rapid phenotypic shift away from IgD expression in resting B cells. Irradiated, non‐transforming virions were also effective in bringing about such change 15 …”
Section: Discussionmentioning
confidence: 99%
“…Irradiated, non-transforming virions were also effective in bringing about such change. 15 Thorley-Lawson has suggested that the naõ Ève B cell constitutes the primary target for EBV infection and that the subsequently transformed lymphoblast then follows the normal differentiation pathway engaged during a T-dependent antigen response, eventually becoming a long-lived memory cell. 16 This is partly based on the analysis of different subpopulations isolated from tonsil.…”
Section: Ebv Infects and Establishes Lifelong Latency In B Lymphocytesmentioning
confidence: 99%
“…EBNA 2 and 5 may play an important role in the early activation of B cells during primary EBV infection Moss et al, 1986;Dillner et al, 1986;Finke et a/., 1987) and in the transformation of B cells. Virus variants that have deletions in the sequences corresponding to the EBNA 2 gene and part of the EBNA 5 gene can partially activate B cells (Hu et al, 1986) but are incapable of transforming B cells (Menezes et al, 1975;Jones et al, 1984;Ernberg et al, 1986). EBNA 2 has also been implied in the regulation of differentiated B-cell functions Cohen et independent of other EBNAs and that EBNA 1 is the only Wang et al, 1987~).…”
Section: Discussionmentioning
confidence: 99%